A further insight into the sialome of the tropical bont tick, Amblyomma variegatum - Ribeiro, José MC (BioMed Central, 2011)
BACKGROUND: Ticks--vectors of medical and veterinary importance--are themselves also significant pests. Tick salivary proteins are the result of adaptation to blood feeding and contain inhibitors of blood clotting, platelet aggregation, and angiogenesis, as well as vasodilators and immunomodulators. A previous analysis of the sialotranscriptome (from the Greek sialo, saliva) of Amblyomma variegatum is revisited in light of recent advances in tick sialomes and provides a database to perform a proteomic study. RESULTS: The clusterized data set has been expertly curated in light of recent reviews on tick salivary proteins, identifying many new families of tick-exclusive proteins. A proteome study using salivary gland homogenates identified 19 putative secreted proteins within a total of 211 matches. CONCLUSIONS: The annotated sialome of A. variegatum allows its comparison to other tick sialomes, helping to consolidate an emerging pattern in the salivary composition of metastriate ticks; novel protein families were also identified. Because most of these proteins have no known function, the task of functional analysis of these proteins and the discovery of novel pharmacologically active compounds becomes possible.